EVALUASI DAN PENGUKURAN KEBERHASILAN USAHA PENDIDIKAN BERBASIS KEWIRAUSAHAAN - Takdirmin; Syarkawi Amin Syukur; Prasetya, Aldian Dwi; Hasim, Nur Fadilah; Amalia, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a strategic sector requiring professional, entrepreneurship-based governance in the era of globalization. This article aims to elaborate on the concept of evaluation, measurement methods, and success indicators for educational ventures. Employing a qualitative approach with a literature review design, data was collected from journal articles, books, and seminar proceedings via databases like Google Scholar, then analyzed using qualitative content analysis. The findings indicate that evaluation is a vital component assessing the success, effectiveness, and efficiency of educational programs, covering managerial to operational aspects. Various evaluation models such as Goal-Oriented, Goal-Free, Responsive Evaluation, and CIPP are relevant. The success of educational ventures is measured not only by academic or financial achievements but also by non-financial indicators like motivation, creativity, development strategies, and extensive networks. In conclusion, systematic and holistic evaluation is crucial for educational institutions to adapt and achieve objectives effectively and sustainably. Recommendations include broadening success indicators, adapting appropriate evaluation models, enhancing evaluator competence, strengthening networks, and conducting further empirical research.